Prevalence of contact allergy in the general population in different European regions - Diepgen, Thomas L.; Ofenloch, Robert; Bruze, M.; Bertuccio, P.; Cazzaniga, S.; Coenraads, P.-J.; Elsner, P.; Goncalo, M.; Svensson, Å; Naldi, L. (British journal of dermatology, 2016)
Background Population-based studies about contact allergy are scarce. Objectives To obtain reliable estimates of the prevalence of contact allergy in the general population in Europe. Methods A cross-sectional study of a random sample from the general population, aged 18-74 years, in five different European countries (Sweden, the Netherlands, Germany, Italy and Portugal). In total, 12 377 subjects were interviewed and a random sample (n = 3119) patch tested to TRUE Test panels 1-3 and Fragrance Mix (FM) II, hydroxyisohexyl 3-cyclohexene carboxaldehyde (HICC) and sesquiterpene lactone mix. A positive patch test reaction is considered as contact allergy. Results In total, 27·0% [95% confidence interval (CI) 25·5-28·5] had at least one positive reaction to an allergen of the European baseline series, with a significantly higher prevalence in women than in men. The highest age-standardized prevalences (≥ 1%) were found for nickel (14·5%, 95% CI 13·2-15·8), thiomersal (5·0%, 95% CI 4·2-5·8), cobalt (2·2%, 95% CI 1·7-2·7), FM II (1·9%, 95% CI 1·5-2·5), FM I (1·8%, 95% CI 1·4-2·3), HICC (1·4%, 95% CI 1·0-1·9), p-tert-butylphenol formaldehyde resin (1·3%, 95% CI 0·9-1·7) and para-phenylenediamine (1·0%, 95% CI 0·6-1·3). Only nickel and thiomersal showed a statistically significantly different prevalence for contact allergy among the different European populations. Subjects reporting contact dermatitis in their lifetime (age-standardized prevalence 15·1%, 95% CI 13·8-16·3) had an increased risk for contact allergy (odds ratio 1·9, 95% CI 1·5-2·5). The risk of having a contact allergy was not increased in those with atopic dermatitis (prevalence 7·6%, 95% CI 6·7-8·6; odds ratio 1·0, 95% CI 0·7-1·4). Conclusions Contact allergy to at least one allergen of the European baseline series was diagnosed in more than one-quarter of the general European population. Therefore measures to improve the primary prevention of contact allergy have to be enforced.
First published: 15 September 2015
Gesehen am 08.05.2020